2010
DOI: 10.1002/ccd.22370
|View full text |Cite
|
Sign up to set email alerts
|

The amplatzer vascular plug and amplatzer vascular plug II for vascular occlusion procedures in 50 patients with congenital cardiovascular disease

Abstract: Plugs 1 and 2 are safe and effective devices that can be used in a variety of blood vessels in patients with CCVD. Plug 2 is particularly useful in closure of high-flow, tubular structures, especially type C PDA's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
2
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 25 publications
10
68
2
6
Order By: Relevance
“…In the literature we have found that transcatheter closure of PDA with AVPII was described only in children (the oldest one was 4 years old) [8,9]. We have confirmed that the Amplatzer plug II is also useful for closure of a relatively large elongated type of PDA in an adult patient.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In the literature we have found that transcatheter closure of PDA with AVPII was described only in children (the oldest one was 4 years old) [8,9]. We have confirmed that the Amplatzer plug II is also useful for closure of a relatively large elongated type of PDA in an adult patient.…”
Section: Discussionsupporting
confidence: 52%
“…Using the AVPII we found that the device was easily delivered through a small catheter (6 F) into the centre of the duct, leading to complete occlusion without obstruction of the aorta or the left pulmonary artery. The approach to AVPII delivery was to have all discs contained within the ductus when possible or (as in our case) to have two discs within the duct and one disc opened in the pulmonary artery [9]. Such a strategy was due to the presence of the relatively long PDA (20 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports of perventricular approaches to close the pulmonary artery stump [8] as well as multiple publications describing vascular occluders for other indications including AV malformations, aorto-pulmonary collaterals, and coronary fistula [9].…”
Section: Discussionmentioning
confidence: 99%
“…All four types of AVP have two components: a vascular plug and a delivery wire. The plugs have radiopaque platinum marker bands at both ends (4). The AVP 2 contains a more densely woven nitinol mesh and minimizes migration and recanalization (5).…”
mentioning
confidence: 99%